Highly enantioselective Michael addition reactions with new trimeric chiral phase transfer catalysts. (20th February 2015) - Beneto, Arockiam Jesin; Sivamani, Jayaraman; Ashokkumar, Veeramanoharan; Balasaravanan, Rajendiran; Duraimurugan, Kumaraguru; Siva, Ayyanar
Abstract : New types of mesitylene based tri-site containing asymmetric quaternary ammonium salts9 (9a and9b ) were synthesized and their catalytic activities were studied using Michael addition reactions with various chalcones and diethylmalonate under mild basic conditions with very good yields and ee's. Abstract : New types of mesitylene based tri-site containing asymmetric quaternary ammonium salts9a and9b have been prepared and used as efficient chiral phase transfer catalysts for enantioselective Michael addition reactions between the chalcones and diethylmalonate under mild reaction conditions such as lower concentration of base, catalyst and ultrasonic conditions with very good chemical yields (up to 98%) and ee's (up to 99%).